INDEX OF THE ARTICLES PUBLISHED IN THE JOURNAL “RATIONAL PHARMACOTHERAPY IN CARDIOLOGY” IN 2009 (Рациональная фармакотерапия в кардиологии, 2016)
Index of the articles published in the journal “Rational Pharmacotherapy in Cardiology” in 2009.